ChemInform Abstract: Active Biopolymers in Green Non‐Conventional Media: A Sustainable Tool for Developing Clean Chemical Processes. Issue 6 (21st January 2016) - Lozano, Pedro; Bernal, Juana M.; Nieto, Susana; Gomez, Celia; Garcia‐Verdugo, Eduardo; Luis, Santiago V.
Abstract: Review: [106 refs.